2015
DOI: 10.1021/acs.jpclett.5b02513
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Phosphorene and Graphene Heterostructure as Anode Materials for Rechargeable Li Batteries

Abstract: There is a great desire to develop the high-efficient anodes materials for Li batteries, which require not only large capacity but also high stability and mobility. In this work, the phosphorene/graphene heterostructure (P/G) was carefully explored based on first-principles calculations. The binding energy of Li on the pristine phosphorene is relatively weak (within 1.9 eV), whereas the phosphorene/graphene heterostructure (P/G) can greatly improve the binding energy (2.6 eV) without affecting the high mobilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
179
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(190 citation statements)
references
References 58 publications
9
179
1
1
Order By: Relevance
“…32 Recently, phospherene, the 2D analog of black-P and phosphorene based hybrid materials have shown great potential as an anode material in Li ion battery. 33,34 However high reactivity of phosphorene towards O 2 and H 2 O still poses important technological bottlenecks. 35 Recently we have shown that capping of hexagonal Boron nitride (h-BN) enhances performance of black phosphorene as an anode material.…”
Section: Introductionmentioning
confidence: 99%
“…32 Recently, phospherene, the 2D analog of black-P and phosphorene based hybrid materials have shown great potential as an anode material in Li ion battery. 33,34 However high reactivity of phosphorene towards O 2 and H 2 O still poses important technological bottlenecks. 35 Recently we have shown that capping of hexagonal Boron nitride (h-BN) enhances performance of black phosphorene as an anode material.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorene based heterostructures have been used to develop novel devices for nanoelectronic applications in recent past e.g. STM images of h-BN/phosphorene heterostructure with h-BN as a capping layer is useful to distinguish between different structural phases of phosphorene [20]; phosphorene/MoS2 acts as CMOS inverter [21] with its possible use as a channel material for electronic applications [22]; phosphorene/graphene heterostructure display potential application as electrode materials for batteries [23]; metal/black-phosphorene heterostructures such as Zn/BP and In/BP forms Schottkey contacts while Cu/BP forms ohmic contact [24] in devices. Similarly, heterostructures based on MoSe2 are also found to be suitable for device applications such as the MoSe2/graphene heterostructures show rapid transfer of photogenerated charge carriers between MoSe2 and graphene which depicts its possible applications in optoelectronics [25]; black phosphorene/MoSe2 heterostructure show potential applications in p-n diodes and logical devices [26];etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are several researches about heterostructure of black phosphorus and other materials. Guo et al [69] presented the phosphorene and graphene heterostructure as anode materials for rechargeable lithium batteries. Based on first-principles calculations, high mobility and stability of heterostructure anode were identified.…”
Section: Black Phosphorus-based Heterostructure and Its Potential mentioning
confidence: 99%